PENGARUH SERVICE QUALITY, PRODUCT QUALITY DAN PERCEIVED VALUE TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN INDUSTRI KAYU PERHUTANI - Gultom, Winarni Saftarya Timedina; Yuliati, Lilik Noor; Djohar, Setiadi (Jurnal Manajemen dan Agribisnis, 2016)
The purpose of this research is to analyze the influences of service quality, product quality and perceived value on the satisfaction and loyalty of the customers of Perhutani wood industry, the level of customer satisfaction and loyalty and managerial implications. Four data analysis techniques were used including the structural equation modeling partial least squares (SEMPLS) with 24 exogenous latent variable attributes and 6 endogenous latent variable attributes; CSI, CLI and IPA. SEMPLS results showed that the variables of service quality (T-statistic=2, 79*>T-table=1, 96) and product quality (T-statistic=6, 45*>T-table=1, 96) significantly influence the satisfaction of the customers of Perhutani wood industry. Perceived value variable (T-statistic=0, 65